Comparison of neutrophil- lymphocyte ratio and platelet-lymphocyte ratio in unstable angina pectoris and non-ST-segment / ST-segment elevation myocardial infarction: a cross-sectional study - Sahitra Sahitra; I Wayan Gustafa; I Putu Parwata Jaya (Department of Anatomy, Medical Faculty, Universitas Udayana, Bali-Indonesia, 2021)
Background: Chest pain is a common complaint that physicians meet in the emergency department. There is a lot of cause of chest pain that originates from a cardiac problem. Coronary heart disease is proven to be one of the most threatening. Inflammation is an essential key in atherosclerosis which triggers acute coronary syndrome. Aim: This study is aimed to investigate the neutrophil-lymphocyte ratio (NLR) and platelet-lymphocyte ratio (PLR) in unstable angina pectoris and non-ST segment / ST-segment elevation myocardial infarction (NSTEMI) in acute coronary syndromes. Method: A medical records-based retrospective cross-sectional study of 141 patients was applied on three groups: unstable angina, NSTEMI, and STEMI for measuring NLR and PLR ratios. Results: There was a significant difference of NLR variable between unstable angina and NSTEMI, STEMI groups (p < 0.001), however, we did not find a substantial difference of PLR count between unstable angina, NSTEMI, and STEMI groups (p < 0.059). Conclusion: NLR count is significantly higher in myocardial infarction than in unstable angina. There is no difference in PLR count between unstable angina and myocardial infarct groups.